Results of a self-assessment tool to assess the operational characteristics of research ethics committees in low- and middle-income countries. Issue 4 (19th April 2014) - Silverman, Henry; Sleem, Hany; Moodley, Keymanthri; Kumar, Nandini; Naidoo, Sudeshni; Subramanian, Thilakavathi; Jaafar, Rola; Moni, Malini
Abstract : Purpose: Many research ethics committees (RECs) have been established in low- and middle-income countries (LMICs) in response to increased research in these countries. How well these RECs are functioning remains largely unknown. Our objective was to assess the usefulness of a self-assessment tool in obtaining benchmarking data on the extent to which RECs are in compliance with recognised international standards. Methods: REC chairs from several LMICs (Egypt, South Africa and India) were asked to complete an online self-assessment tool for RECs with a maximum score of 200. Individual responses were collected anonymously. Results: The aggregate mean score was 137.4±35.8 (∼70% of maximum score); mean scores were significantly associated with the presence of a budget (p<0.001), but not with duration of existence, frequency of meetings, or the presence of national guidelines. As a group, RECs achieved more than 80% of the maximum score for the following domains: submission processes and documents received, recording of meeting minutes, criteria for ethical review and criteria for informed consent. RECs achieved less than 80% of the maximum score for the following domains: institutional commitment, policies and procedures of the REC, membership composition and training, policies and procedures for protocol review, elements of a decision letter and criteria for continuing review. Conclusions: This study highlights areas where RECs from LMICs can improve to be in compliance with recommended international standards for RECs. The self-assessment tool provides valuable benchmarking data for RECs and can serve as a quality improvement method to help RECs enhance their operations.